Analysis of the special case of binary separation at source of municipal solid waste with the help of analytical hierarchy process in terms of environmental, economic, social and technical criteria - Apaydin, Omer (PAMUKKALE UNIV, 2025)
The aim of this study is to decide on the municipal solid waste (MSW) management option for the minimum criterion of Zero Waste Regulation (ZWR) which is binary separation at source. To achieve this aim, analytical hierarchy process (AHP) was used as a multi-criteria decision-making tool. Five different waste management alternatives were selected as decision points. The main criterion affecting the decision points was binary separation of solid waste at source, and five environmental, four economic, three social and three technical criteria were selected as sub-criteria. Expert opinions were consulted to obtain binary comparison data both within the sub-criteria themselves and for each criterion ofMSWmanagement alternatives. The survey prepared using Google Forms. Using the geometric means of the numerical data obtained from expert opinions, binary comparison matrices were created for each sub-criteria group within the scope of the ZWR minimum criterion and the necessary AHP analysis processes were applied. According to the results obtained; MSW management alternative preferences were calculated as material recovery(0.381)> thermal process(0.193)> biomethanization(0.187)> composting(0.125)> sanitary landfill(0.112) for environmental; sanitary landfill(0.357)> material recovery(0.247)> composting(0.193)> biomethanization(0.097)> thermal process (0.054) for economic; material recovery(0.393)> composting(0.233)= biomethanization(0.233)> thermal process(0.086)> sanitary landfill(0.055) for social; material recovery (0.381)> sanitary landfill(0.315)> composting(0.143)> biomethanization (0.114)> thermal process (0.047) for technical criteria. As a result; in case of applying binary separation at source, it has been determined that the priority of domestic solid waste management alternative is material recovery in terms of environmental, social and technical criteria, and sanitary landfill in terms of economic criteria.
Keywords: Binary separation at source; Analytical hierarchy process; Google forms survey; Solid waste management alternatives; Zore waste reaction; MANAGEMENT-SYSTEM; SMART CITIES; AHP; Engineering